Oxygen suppression of macroscopic multicellularity - G. Ozan Bozdag (Nature Portfolio, 2021)
The evolution of multicellular life is hypothesized to have been promoted by rising oxygen levels. Through experimental evolution and modeling, Bozdag et al. demonstrate that our planet’s first oxygenation would have strongly constrained, not promoted, the evolution of multicellular life.